Faculty perception of medical council of India basic course workshop in medical education technologies as faculty development programme - Yadav, Arvind Kumar; Choudhary, Savita (International Journal of Basic & Clinical Pharmacology, 2016)
Background: There is growing recognition of the importance of basic course workshop (BCW) in medical education technologies (MET) implemented by MCI as faculty development programme. It is now mandatory by the MCI for all the faculty members from Professor to Assistant Professor. So, this study was planned to develop a questionnaire and to use this questionnaire after validation as a tool to assess faculty perception of BCW in MET. Methods: This is a questionnaire based observational study. After taking the ethical permission from the institutional ethical committee, data was collected in preformed validated questionnaire from all the faculty members who have undergone the basic course workshop at our institute. Results: Out of total 60 faculty who responded to the questionnaire 50 (83.33) were showing positive response on compulsion of MCI BCW for all faculties and 42 (70%) faculties considered it during post-graduation itself. 56 (93.33%) accepted that this course was beneficial in acquiring new concepts or knowledge. 46 (76.66%) out of total 56 (93.33%) faculty who acquired new knowledge said that they have implemented new acquired knowledge in routine practice and 41 (68.33%) found positive response in students. Only 17 (28.33%) attended workshop for certificate and promotion consequences in future. 31 (51.66%) faculties responded that present modules requires certain changes and 51 (85%) think that implementation of some part of modules require more teaching faculty in department. Conclusions: BCW must be an integral part of the faculty development programme at institute level but its modules should be regularly updated time to time.